Value-Added Erosion in Global Value Chains: An Empirical Assessment. Issue 1 (2nd January 2016) - Caraballo, José G.; Jiang, Xiao
Abstract: In the period from 1995 to 2008, many countries experienced what we call the "value-added erosion." It describes the decline in the sectoral shares of domestic value-added in a country's exports as the country becomes more integrated into the global value chains (GVCs). We argue that the decline of the domestic value-added share in a country's exports is likely to be caused by the expansion of high value-adding activities performed by foreign lead firms in the upper stream of the GVCs. The variables of interest — the domestic value-added share in exports and foreign high-skill labor embodied in a country's exports (a proxy for foreign lead firms' high value-adding activities) — are estimated using a multi-regional global input-output model. Using these results and other control variables, we apply a panel cointegration model to explain and assess the likelihood of value-added erosion and its possible determinants.